2019
DOI: 10.1155/2019/8613523
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Mechanism of Curcumin Regulating Lung Injury Induced by Outdoor Fine Particulate Matter (PM2.5)

Abstract: Background. Epidemiological studies have shown that exposure to PM induces oxidative stress, leading to a variety of health problems. In particular, PM2.5 contains a lot of substances harmful to the human body and penetrates into the lungs to induce lung injury. At the same time, there is increasing evidence that oxidative stress also affects the severity of lung injury. However, there is still no good way to reduce or eliminate these hazards. In the future, more experimental research is needed to further conf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 54 publications
2
39
0
Order By: Relevance
“…Meanwhile, in our in vitro study, elevated levels of ROS were observed in the H9C2 cells exposed to UFPM, consistent with an imbalance in the oxidation/reduction observed in our in vivo study. A previous study demonstrated a significant difference in the expression levels of MDA, CAT, and GSH-Px in lung tissues of PM2.5-treated mice compared with saline-treated control mice ( Huang et al, 2019 ). Similar increases in the levels of HO-1 and NOX in the lung and heart have been reported after particle exposure in rats; the differences were dependent on particulate size ( Aztatzi-Aguilar et al, 2015 ).…”
Section: Discussionmentioning
confidence: 93%
“…Meanwhile, in our in vitro study, elevated levels of ROS were observed in the H9C2 cells exposed to UFPM, consistent with an imbalance in the oxidation/reduction observed in our in vivo study. A previous study demonstrated a significant difference in the expression levels of MDA, CAT, and GSH-Px in lung tissues of PM2.5-treated mice compared with saline-treated control mice ( Huang et al, 2019 ). Similar increases in the levels of HO-1 and NOX in the lung and heart have been reported after particle exposure in rats; the differences were dependent on particulate size ( Aztatzi-Aguilar et al, 2015 ).…”
Section: Discussionmentioning
confidence: 93%
“…Another recent study was done by Huang et al 2019, where traffic-based PM2.5 was instilled into mouse trachea as a PM2.5-induced injury. In this paper, the authors found lung injury to be the result of oxidative damage and induction of inflammatory processes (Huang et al, 2019). These are just a few current studies, but PM2.5 continues to be a popular area of environmental research.…”
Section: Particle Size and Its Effect On Lung Functionmentioning
confidence: 99%
“…Unlike PM 10 , PM 2.5 is su ciently small in size to reach the alveoli of the lungs, thus exhibits a signi cant impact on human health [1][2][3][4]. According to the Global Burden of Disease report, airborne PM 2.5 exposure might contribute to 4.2 million deaths and 100 million disability-adjusted life-year losses, and serves as the fth largest risk factor for death in the world [5]. Epidemiological studies have consistently shown that long-term exposure to high levels of PM 2.5 is associated with high risks of ischemic heart disease, stroke, lung cancer, and chronic obstructive pulmonary disease [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous evidences suggested that oxidative stress and in ammation play a critical role in PM 2.5 induced lung injury [5,[8][9][10]. Exposure to PM 2.5 has been reported to stimulate the release of various proin ammatory molecules in the lung.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation